1998
DOI: 10.1253/jcj.62.341
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Magnesium Administration on Decreased Exercise Tolerance in a State of Chronic Sleep Deprivation

Abstract: We have previously reported that chronic sleep deprivation causes a deficiency of intracellular magnesium (Mg) and decreased exercise tolerance. The aim of this study was to clarify whether oral administration of Mg could be effective in restoring the exercise tolerance that is decreased by chronic sleep deprivation. A bicycle ergometer cardiopulmonary exercise test was performed by 16 healthy volunteers (mean age 21.9 years). They were divided into 2 groups: 8 received doses of 100 mg of Mg orally per day for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…19 In addition, both experimental and human studies revealed that mental and psychosocial stress decrease endothelial function. 11,20,21 According to Tanabe et al 's reports,4,6 the decreased levels of intracellular magnesium in this study were identical to those between temporary and persistent sleep deprivative conditions; they are thus considered to be a reflection of sleep deprivation in our study protocol.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…19 In addition, both experimental and human studies revealed that mental and psychosocial stress decrease endothelial function. 11,20,21 According to Tanabe et al 's reports,4,6 the decreased levels of intracellular magnesium in this study were identical to those between temporary and persistent sleep deprivative conditions; they are thus considered to be a reflection of sleep deprivation in our study protocol.…”
Section: Discussionsupporting
confidence: 79%
“…Sleep deprivation has been reported to decrease the intracellular magnesium level in humans, 4,6 and mental stress has also recently been reported to cause transient endothelial dysfunction in the brachial artery in humans; 11 however, the relationship between intracellular magnesium levels and endothelial function has not yet been fully investigated. Magnesium is considered to be a physiologic calcium antagonist and has been reported to decrease vascular tone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnesium has a favourable effect with respect to sleep onset and maintenance and also tiredness, which appears as a consequence of sleep deprivation. In their studies of chronic sleep deprivation, Tanabe et al, (1998) reported a reduction of intracellular magnesium level. This reduction was associated with a decreased exercise tolerance.…”
Section: Relationship Between Magnesium and Neurosesmentioning
confidence: 99%